2002
DOI: 10.1097/00008506-200204000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Pain Management After Supratentorial Craniotomy

Abstract: The aim of this study was to compare the analgesic efficacy of three different postoperative treatments after supratentorial craniotomy. Sixty-four patients were allocated prospectively and randomly into three groups: paracetamol (the P group, n = 8), paracetamol and tramadol (the PT group, n = 29), and paracetamol and nalbuphine (the PN group, n = 27). General anesthesia was standardized with propofol and remifentanil using atracurium as the muscle relaxant. One hour before the end of surgery, all patients re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(58 citation statements)
references
References 14 publications
1
54
0
3
Order By: Relevance
“…Ten percent of craniotomy patients had severe postoperative pain or required more than 10 mg of morphine in the postanaesthetic care unit. Most recent reports have suggested that pain is a greater problem than previously considered, with 40-60% of patients having moderate to excruciating pain [3][4][5][6]. A recent review article [7] identified acute postoperative pain as an important clinical problem which has been comparatively neglected, and found that chronic pain resulting from intracranial surgery has received scant attention, with a paucity of data on its incidence and management.…”
mentioning
confidence: 99%
“…Ten percent of craniotomy patients had severe postoperative pain or required more than 10 mg of morphine in the postanaesthetic care unit. Most recent reports have suggested that pain is a greater problem than previously considered, with 40-60% of patients having moderate to excruciating pain [3][4][5][6]. A recent review article [7] identified acute postoperative pain as an important clinical problem which has been comparatively neglected, and found that chronic pain resulting from intracranial surgery has received scant attention, with a paucity of data on its incidence and management.…”
mentioning
confidence: 99%
“…In this case the addition of tramadol or nalbuphine to paracetamol seems to be necessary, with the drawback of a greater incidence of nausea and vomiting 44 .…”
Section: Postoperative Carementioning
confidence: 99%
“…Certainly, for supratentorial craniotomy using a propofol-remifentanil anesthetic, acetaminophen alone is inadequate [106], but when combined with tramadol or nalbuphine administered on an ''as needed'' (PRN) basis both combinations were equally effective, resulting in mild pain for the first 24 postoperative hours. Several studies have compared intramuscular codeine phosphate with morphine sulfate.…”
Section: Analgesic Therapy Following Intracranial Surgerycurrent Pracmentioning
confidence: 99%